Pengembangan LKPD dengan Pendekatan STEM untuk Meningkatkan Keterampilan Berpikir Kritis Siswa pada Pembelajaran IPA SMP - Dzulkifli Nurul Huda (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The critical thinking skills of junior high school students in Indonesia are still relatively low. The reason for this low skill is because the teaching materials used are still not relevant and have not specifically focused on improving critical thinking skills. The purpose of this study is to examine the validity, practicality, and effectiveness of LKPD with the Science, Technology Engineering, Mathematics (STEM) approach in improving the critical thinking skills of junior high school students. The method used is Research and Development (R&D) using the ADDIE model development design which includes analyze, design, develop, implement, and evaluate. Data collection techniques use LKPD validation sheets, learning implementation sheets, pre-test and post-test questions and student response questionnaires. The results of the validity of LKPD with the STEM approach obtained a validity value of 93% (very valid category) indicating that LKPD with the STEM approach is easy to use by teachers and students. Practicality is assessed through student activity sheets, with a result of 89% (very practical category). Student response questionnaires with a value of 84%, which shows a positive response from students. It can be concluded that LKPD with the Science, Technology, Engineering, Mathematics (STEM) approach that was developed is effective and feasible to be used in improving critical thinking skills of junior high school students
Reaploud Repository Hasyim April 2026
Keywords: Critical Thinking Skills; LKPD; STEM.